PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA PERUSAHAAN PERBANKAN - Heni Swastika; Titik Aryati (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
This Thesis is done in order to give empirical prove about Corporate Social Responsibily (CSR) related to Company Financial Performance (productivity and value of a company). In this Thesis, company's performance devided in short term performance and long term performance. Company's short term performance is company's productivy based on Asset Turnover (ATO), while Company's long term pe4formance is company's value based on Price to Book Value (PBV). Corporate Social Reponsibility (CSR) performance is measured with Sustainability Report Disclosure Index (SRDI). Population used in this thesis is the company that have been registered in Bursa Efek Indonesia (BEI) in a certain period between 2012 until 2014. Total sample for this Thesis are 31 Banking company which is chosen using purposive sampling method. The data for this thesis is analyzed using classical assumption test and hypothesis test using Doubled Linear Regression. This research proves that Corporate Social Responsibility (CSR) brings positive effect related to Productivity of a Company and Value of a Company.